Medium-term outcome of liver recipients from COVID-19 donors. (March 2023) - Saracco, M.; Cocchis, D.; Tandoi, F.; Rigo, F.; Romagnoli, R.; Martini, S.
Abstract : Background: COVID-19 is associated with thrombotic complications and can result in hepatobiliary injury. Excellent early outcomes have been reported in recipients of solid non-lungs organs from SARS-CoV-2-infected donors, however longer follow-up data are lacking. We aimed to describe the medium-term outcome of our liver transplants (LT) from COVID-19 donors. Methods: From 11/2020 to 03/2022, we consecutively enrolled all patients who received a graft from COVID-19 donor in our Centre. Protocol liver biopsy and magnetic resonance cholangiopancreatography (MRCP) after 1-year from LT were reported. Results: In the study period 12/213 (5.6%) adult LT patients received a COVID-19 donor (11 active, 1 resolved COVID-19) 1 . Eleven patients underwent end-to-end biliary anastomosis and 1 biliodigestive anastomosis. Recipients' and donors' characteristics are reported in table 1 . Two recipients tested SARS-CoV-2 RNA positive on nasopharyngeal swab at LT and one was treated with sotrovimab on day-1 after LT. None of the patients developed COVID-19 after LT. One patient underwent hepatic artery thrombectomy at day-1 and died after 320 days for HCC recurrence. Until now: -10 patients underwent protocol MRCP (median time from LT 562 days, IQR 245-614), which showed: 7 no visible abnormalities, 1 donor-recipient's bile duct size discrepancy, 2 caliber changes <50% at the anastomotic level (untreated for the absence of cholestasis); -7 patients underwent protocol liver biopsy (median time from LT 553 days, IQR 311-557) which showed 1 acute cellular rejection (RAI 4/9) successfully treated with steroids; no signs of fibrosis, rejection or biliopathy in the other 6 patients. Conclusions: 11/12 patients who received a LT from COVID-19 donors are alive, without evidence of SARS-CoV-2 transmission. At a median follow-up of 1.5 years, protocol liver biopsy and MRCP did not show biliopathy, supporting the utilization of COVID-19 donors to expand the donor pool and reduce the waiting list mortality.